2013
DOI: 10.1007/s10803-013-1973-x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Problems in Children with Autism, Developmental Delays or Typical Development

Abstract: SCIENTIFIC ABSTRACT Objectives To compare GI problems among children with: 1) autism spectrum disorder (ASD), 2) developmental delay (DD) and 3) typical development (TD). Methods In 960 children from the CHildhood Autism Risks from Genetics and the Environment (CHARGE) study, we assessed GI symptom frequency. We examined scores on five Aberrant Behavior Checklist subscales comparing ASD children with high vs. low frequency GI symptoms. Results Compared to TD children, those with ASD (aOR 7.92[4.89–12.85])… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
340
2
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(367 citation statements)
references
References 19 publications
10
340
2
15
Order By: Relevance
“…Some studies have observed that gastrointestinal (GI) problems are common in ASD and, even though the results are contrasting, food selectivity may contribute to GI problems in a portion of these individuals (Chaidez, Hansen, & Hertz-Picciotto, 2014;Gorrindo et al, 2012;Horvath & Perman, 2002;Ibrahim, Voigt, Katusic, Weaver, & Barbaresi, 2009;Maenner et al, 2012;Mazefsky, Schreiber, Olino, & Minshew, 2014;Mazurek et al, 2013;Mouridsen, Isager, & Rich, 2013;Nikolov et al, 2009;Valicenti-McDermott, McVicar, Cohen, Wershil, & Shinnar, 2008;Whitehouse, Maybery, Wray, & Hickey, 2001). Furthermore, it has been suggested that sensory processing problems, such as sensory sensitivity, which are common among individuals with ASD, could be possible mechanisms underlying food selectivity (Cermack, Curtin, & Bandini, 2010;Mazurek et al, 2013;Suarez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have observed that gastrointestinal (GI) problems are common in ASD and, even though the results are contrasting, food selectivity may contribute to GI problems in a portion of these individuals (Chaidez, Hansen, & Hertz-Picciotto, 2014;Gorrindo et al, 2012;Horvath & Perman, 2002;Ibrahim, Voigt, Katusic, Weaver, & Barbaresi, 2009;Maenner et al, 2012;Mazefsky, Schreiber, Olino, & Minshew, 2014;Mazurek et al, 2013;Mouridsen, Isager, & Rich, 2013;Nikolov et al, 2009;Valicenti-McDermott, McVicar, Cohen, Wershil, & Shinnar, 2008;Whitehouse, Maybery, Wray, & Hickey, 2001). Furthermore, it has been suggested that sensory processing problems, such as sensory sensitivity, which are common among individuals with ASD, could be possible mechanisms underlying food selectivity (Cermack, Curtin, & Bandini, 2010;Mazurek et al, 2013;Suarez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported the prevalence of GI problems, one of common comorbid conditions of ASD [83,84]. Accumulat-ed findings lead to the hypothesis of gut-brain axis, which suggests that gut microbiota can alter brain activity through endocrinal, metabolic or immunological mechanisms, and can possibly induce the pathogenesis of ASD [85][86][87][88].…”
Section: Gastrointestinal Microbiota In Asdmentioning
confidence: 99%
“…In their comparison, Chaidez and coworkers found that parents of children with ASD or developmental delay reported more food dislikes (selectivity), as well as more GI symptoms not explained by other factors, than parents of typically developing children (9). Their results also show significantly higher incidence of behavioural problems (irritability, social withdrawal, stereotypy and hyperactivity) in ASD children with GI problems than those without symptoms.…”
Section: Introductionmentioning
confidence: 96%
“…Although Kuddo and Nelson concluded that the frequency of gastrointestinal problems are much less frequent in children with autism than pediatric gastroenterology clinics report (6), several authors have found a strong association between bowel problems and autism in community samples (7)(8)(9). Specific symptoms, such as diarrhoea, constipation, foul-smelling stools, flatulence, abdominal bloating and discomfort have been identified and compared between children with autism and their healthy siblings (10,11).…”
Section: Introductionmentioning
confidence: 99%